Efficacy of Medicinal Leech Therapy in Diverse Clinical Applications: A Comprehensive Study from Azerbaijan - Farzali, Shabnam; Yaraliyeva, Sudaba; Huseynov, Fizuli; Manafov, Asif; Sağlam, Naim (Galenos Publishing House, 2025)
Objective: Hirudotherapy (HT), the therapeutic use of medicinal leeches, has been practised for centuries, and the interest in modern medicine has recently been renewed. This study evaluates the clinical outcomes of HT at Herba Medical Center in Azerbaijan between 2020 and 2024, focusing on its efficacy across 11 medical conditions. Methods: A total of 181 patients were treated using disposable medicinal leeches (Hirudo orientalis) sourced from hygienic farms approved by Azerbaijan’s Ministry of Ecology and Natural Resources. Treatment protocols were tailored to disease severity, with sessions scheduled daily, every 3 days, or weekly, depending on the condition. Success rates were calculated based on post-treatment examinations, patient feedback, and physician evaluations. Statistical analyses, including Pearson correlation analysis and paired t-test, were used to compare treatment success rates between conditions. Results: The overall success rate of HT was found to be 82.68±29.25%. 100% success was achieved in the treatment of osteoarthritis pain (n=50), lipoma (n=8), Raynaud disease (n=3) and scleroderma (n=2). High success rates were also observed in thyroiditis (94.44%, n=18), Baker’s cyst (80%, n=25), ear diseases (80%, n=10) and diabetic foot ulcers (80%, n=5). Moderate success was achieved in eye diseases (75%, n=20), and the lowest efficacy was observed in the treatment of varicose veins (33.33%, n=30). HT effectively relieved pain and improved symptoms. However, it was limited in reversing structural deformities (e.g., hallux valgus) or tissue loss (e.g., diabetic foot ulcers). Conclusion: These findings suggest that HT may have broader indications. We propose that HT can effectively relieve pain, regulate blood circulation, and treat some chronic diseases with fewer side effects. Further and more detailed research is needed to understand the mechanism of this treatment method better. © 2025 Turkish Society for Parasitology.
Çeşitli Klinik Uygulamalarda Tıbbi Sülük Tedavisinin Etkinliği: Azerbaycan’dan Kapsamlı Bir Çalışma
Keywords: chronic diseases; complementary treatment; Hirudotherapy; leech therapy; pain management; traditional medicine